The External Built Form of Drying Area Design In High - Rise Residential Buildings in Malaysia - Leong, Hung Sek (2019)
A simple yet necessity of daily living are to wash and hang laundries to dry. However, in developing countries, adequate drying area or space for laundry in some of the high-rise residential settings are often neglected. In reality, ‘hanging laundry syndrome’ is an act or habit of blatantly exposing laundries in public view along the building perimeter or façade, with some confined to internal space of the buildings such as bathrooms or internal corridors. This not only inconvenient the residents but create unsightly cityscape. This study intends to explore a social phenomenon from perspectives of human habitual practice and it’s inter-relations with the built environment. It will focus on commonly found high-rise residential typologies in Malaysia in discussing the issues and to propose some possible solutions to improve the situation. Data derives mainly from observation study and sampling survey. The analysis from observation findings is discussed in three parts; i.e. Division according to building typologies, layout and how these affect the laundry practices; division following social stratification of public low cost, private middle cost and high-end housing; and observations in selected housing estates. In addition, sampling questionnaire surveys were carried out at properties fairs in three different states. The survey was tabulated mainly in Likert Scale and analyzed through using Chi-Square tests and cross-tabulations; it has concluded that socio-cultural elements are not significant factors influencing the preferences on the laundry practices. This is somewhat in contrast with the observation findings, which identified distinctions in habitual laundry practices within several building topologies and housing categories, i.e. whether public or private initiated or low-income or luxurious types. The study discusses some underlying factors contributing to the dichotomy. The dissertation ends with some preliminary ideas that could be useful in uplifting the current situation. The proposed solutions have taken into considerations criteria on sustainability, costs effectiveness, practicality in mind; and highlight the importance of overall building integrity, form and geometry. The adoption and implementation however, would depend on possible commitment from the society, resident associations, professionals as well as the authorities to resolve the dilemma.